K'awiil : el dios Maya del rayo, la abundancia y los gobernantes - Valencia Rivera, Rogelio, (Paris monographs in American archaeology ;, 2022)
This study of K'awiil analyses one of the most important deities of the Maya pantheon, and allows us to approach the religious thought of this people, since it is through the myths, rituals and other religious and cultural activities in which a deity participates, that we can try to understand how the Maya conceived their universe.